2002
DOI: 10.1055/s-2002-32281
|View full text |Cite
|
Sign up to set email alerts
|

Möglichkeiten und Grenzen der Osteoporoseprävention durch Östrogene und Gestagene

Abstract: Die multifaktorielle Erkrankung Osteoporose zählt heute mit 5 ± 6 Mio. Betroffenen in der BRD zu einer der häufigsten Erkrankungen der postmenopausalen Frau und weist trotz eines erweiterten Spektrums diagnostischer und therapeutischer Möglichkeiten weiterhin eine deutlich zunehmende Inzidenz auf. Hieraus ergibt sich die Notwendigkeit zur frühzeitigen Identifikation von Risikopatienten sowie die Einleitung individuell angepasster Präventionsmaûnahmen. Dazu zählen neben der Motivation zur knochenstoffwechselges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
11

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
0
2
0
11
Order By: Relevance
“…Regarding fractures, about one in two women over the age of 50 is likely to experience such an event in her lifetime (Melton 2002). Estrogen plays a critical role in bone health (Mackey & Joy 2005), which deteriorates with aging (Hadji et al 2002) and accelerates after menopause because of decreased circulating estrogen (Devine et al 2005). Substudies of the Women's Health Initiative Observational Study (NZ93 676) have shown that postmenopausal breast cancer survivors have significantly lower total body bone mineral density (BMD) and total hip BMD (Chen et al 2005a), as well as an increased risk of clinical fracture, compared with women without a history of cancer (Chen et al 2005b).…”
Section: Fractures and Osteoporosismentioning
confidence: 99%
“…Regarding fractures, about one in two women over the age of 50 is likely to experience such an event in her lifetime (Melton 2002). Estrogen plays a critical role in bone health (Mackey & Joy 2005), which deteriorates with aging (Hadji et al 2002) and accelerates after menopause because of decreased circulating estrogen (Devine et al 2005). Substudies of the Women's Health Initiative Observational Study (NZ93 676) have shown that postmenopausal breast cancer survivors have significantly lower total body bone mineral density (BMD) and total hip BMD (Chen et al 2005a), as well as an increased risk of clinical fracture, compared with women without a history of cancer (Chen et al 2005b).…”
Section: Fractures and Osteoporosismentioning
confidence: 99%
“…B. "insulin-like growth factor 1", Interleukin 1 und 6, "transforming growth factor β", Leptin, Neuropeptid Y und der Tumornekrosefaktor [23].…”
Section: Therapieaspekte Benigner Gynäkologischer Erkrankungenmentioning
confidence: 99%
“…Östrogenersatztherapie allein (ERT) oder in Kombination mit einem Gestagen (HRT) wird für die Prävention der postmenopausalen Osteoporose empfohlen [20]. Eine große Zahl von Studien hat in den vergangenen 20 Jahren den positiven Einfluss der Östrogene auf den Knochenstoffwechsel und die Knochendichte an frakturrelevanten Messorten belegt [28].…”
Section: Hormonersatztherapieein Sterbender Schwan?unclassified
“…Frakturdaten liegen nicht vor. Im Rahmen der HRT üben die Gestagene zumindest keinen negativen Effekt auf die Knochendichte aus [20]. Ein knochenprotektiver Effekt der pflanzlichen Östrogene wird zwar postuliert, konnte aber in keiner RCT belegt werden [28].…”
Section: Hormonersatztherapieein Sterbender Schwan?unclassified